Factors influencing online food delivery services among UiTM Cawangan Selangor, Kampus Puncak Alam students / Norzahirah Zaini - Zaini, Norzahirah (2019)
This study examines the factors that influence online food delivery services among the students of UiTM Cawangan Selangor, Kampus Puncak Alam. The factors needs to be achieved from the customers are consist of three elements which are; trust, satisfaction, and loyalty. A survey data of 102 online food delivery customers were used to test the research correlation using Statistical Package for Social Sciences (SPSS). Results reveal a weak significant relationship between the customer experience in the usage of online food delivery services and customer loyalty of online food delivery services. Moreover, the factors of online food delivery services among the students also determine the customer satisfaction that will lead to the trust and loyalty. To conclude, the study provides valuable insights for operation of online food ordering and delivery successfully.